The Impact of Simulation-Based Education on Safe Procedural Sedation Competence and Practice - Momi Gul Khattak (18466425) (2024)
Background The provision of sedation and analgesia to facilitate the performance of painful and/or anxiety-provoking procedures is now a widespread and integral practice for a variety of specialists. The use of appropriate procedural sedation agents for patients undergoing different types of procedures can help reduce mortality rates and associated secondary complications. To provide safe, effective, and patient-centered care, interprofessional healthcare teams should be competent to perform safe procedural sedation. However, due to the need for interprofessional involvement during procedural sedation, it is important to standardize practices. To achieve that, while mitigating clinical practice mistakes, simulation is used to develop competent and confident practitioners. Hamad International Training Center (HITC) developed a simulation-based safe procedural sedation program targeting interprofessional healthcare teams across Qatar who are regularly and directly involved in procedural sedation. This study aims to describe learners’ perceived impact of simulation? based education on safe procedural sedation competence and clinical practice. Methods Course evaluation data was obtained from all doctors, nurses, and allied health practitioners (N=406) who attended the procedural sedation simulation training between January 2021- and August 2023 (Table 1). Descriptive analyses were performed using SPSS version 28. Results The interprofessional simulation-based safe procedural sedation program was perceived to have positively impacted learners with respect to their levels of satisfaction, procedural sedation skills competence, and clinical practices. (Table 2). Conclusion The use of interprofessional simulation-based education can allow learners to develop their safe procedural sedation competence and practice and enhance active learning. The delivery of the course using simulation enabled learners to achieve the intended learning objectives and to be actively engaged with a high level of perceived satisfaction. The use of simulation is recommended for safe procedural skills development and competence enhancement.